2018
DOI: 10.35609/afr.2018.3.1(4)
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance, State Ownership and Firm Performance: An Empirical Study of State-Owned Enterprises in Indonesia

Abstract: Objective - The purpose of this research is to determine the effect of good corporate governance (GCG) on Indonesia's SOEs and the influence of state ownership on company performance. Methodology/Technique - This study examines State Owned Enterprises in Indonesia that were listed on the Indonesia Stock Exchange between 2011 and 2015. Findings - The empirical results show that GCG and state ownership both have a positive influence on the company's financial performance (in this case, Return On Assets). Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 14 publications
1
8
0
2
Order By: Relevance
“…Other than that, we also applied indicators of ownership ( e.g. Eforis C, 2018 ) to assess the effect on SOEs performance. Table 1 shows the variables selected for each category that used in this study.…”
Section: Selection Of the Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than that, we also applied indicators of ownership ( e.g. Eforis C, 2018 ) to assess the effect on SOEs performance. Table 1 shows the variables selected for each category that used in this study.…”
Section: Selection Of the Variablesmentioning
confidence: 99%
“…In contrast, Eforis (2018) conducted research on SOEs in Indonesia that were listed in the Indonesia Stock Exchange (IDX) between 2011 and 2015 to investigate the relationship between state ownership and firm's performance. The authors showed that state ownership has a positive influence on the company's financial performance.…”
Section: Introductionmentioning
confidence: 99%
“…Few studies on the benefits of state ownership have supported efficiency arguments for state ownership, (e.g., police and prison ownership; Hart, Shleifer, & Vishny, 1997). By contrast, most studies have demonstrated that state ownership is inherently inefficient (Eforis, 2018;Lin, Ma, & Su, 2009;Martin & Parker, 1995). First, the agent-principal problem is more prominent under state ownership.…”
Section: Moderating Impact Of Ownership Structurementioning
confidence: 99%
“…Dengan jumlah kompetitor yang akan sangat terbatas diharapkan perusahaan milik negara ini dapat memperoleh laba yang maksimal. Hasil penelitian dari Eforis (2018) dan Zulaikah et al, (2019) menemukan bahwa perusahaan dengan kepemilikan negara mayoritas dapat mencapai kinerja perusahaan yang lebih tinggi karena mendapat dukungan dari pemerintah. Penelitian oleh Liljeblom et al, (2019) dan Chan et al, (2018) menyimpulkan bahwa kepemilikan negara mempunyai pengaruh signifikan negatif terhadap kinerja perusahaan.…”
Section: Kepemilikan Negara Terhadap Kinerja Perusahaanunclassified
“…Penelitian ini sejalan dengan penelitian dari Abramov et al, (2017), Wu et al, (2013), Eforis, (2017) yang juga menujukkan bahwa variabel kepemilikan negara berpengaruh tidak signifikan terhadap kinerja keuagan perusahaan yang diukur dengan ROA. Hasil penelitian ini juga sesuai dengan hasil penelitian dari Eforis, (2018), Saragih, (2013, dan Alipour, (2013) yang menyatakan bahwa variabel kepemilikan negara memiliki dampak signifikan positif dengan kinerja perusahaan yang diukur dengan ROE Akan tetapi hasil dari penelitian ini bertolak belakang dengan hasil penelitian dari Liljeblom et al, (2019), Chan et al, (2018), Zulaikah et al, (2019) yang menemukan bahwa kepemilikan negara berpengaruh signifikan negatif terhadap kinerja perusahaan.…”
Section: Uji Regresi Panelunclassified